Pengaruh Daya Tarik Wisatawan dan Kualitas Pelayanan terhadap Kepuasan Pengunjung di Pemandian Gunung Gajah Lingga Tiga Labuhan Batu Selatan Sumatera Utara - Agustina, Eka; Sulaiman, Fahmi (Universitas Batanghari, 2024)
This study is targeted at observing whether visitor satisfaction at Gunung Gajah Lingga Tiga Baths, South Labuhan Batu Regency is influenced by the quality of services provided and tourist attraction. Using a random sampling method, 99 visitors to Mount Gajah Lingga Tiga Baths in May 2024 were used as the study sample. This means that anyone who happens to meet the researcher can be included in the sample if it is determined that the individual is a suitable data source. Data processing was carried out using SPSS, while data analysis used multiple linear regression testing. The results of the study show that tourist attractions have a partial impact on visitor satisfaction with a t value above the t table (3.001 > 1.984) and a sign of 0.003 < 0.05. Service quality also has a significant positive impact on visitor satisfaction with a t count above the t table (8.299 > 1.984) and a sign of 0.000 < 0.05, but simultaneously tourist attraction and service quality have a significant positive impact on visitor satisfaction with a F count above the F table (164.318 > 3.09) and sign 0.000 < 0.05.